Evolução da osteoporose no paciente com doença pulmonar obstrutiva crônica (DPOC) no intervalo de um ano - Moussalem, Gleice Castrillon de Souza [UNIFESP] (2016)
Introduction: chronic obstructive pulmonary disease (COPD) is characterized by reduced airflow, that can be progressive and chronic inflammation of the lungs. COPD is often associated with comorbidities that contribute to disease severity. Among those comorbidities, is osteoporosis, which is characterized by decreased bone mass accompanied by deterioration of their microstructure, leading to decreased resistance and thus an increased risk of fractures. Early recognition of reduced bone mass in this population of patients is important for the nstitution of measures to minimize the likelihood of falls and fractures. Objective: Evaluate the evolution of bone mineral density in patients with COPD in the one year period and compared with a control group. Materials and Methods: This was a prospective cohort study that evaluated 155 individuals twice with an interval of a year, divided in COPD group and control group. Subjects were assessed with questionnaires, spirometry and bone densitometry. Bone densitometry were acquired femoral neck images, proximal femur and lumbar spine. The diagnosis of osteoporosis was based on T-score values. It was considered as BMD loss when individuals had ariation between follow-up and initial assessment of 0.04 g / cm2 in proximal femur and 0.02 g / cm2 in lumbar spine. Results: There were initially 97 patients with COPD and 85 controls, and after one year were re-evaluated 86 patients with COPD and 69 controls. The COPD group had higher prevalence of osteoporosis (31%) than the control group (18%). In both evaluations the COPD group had lower BMD values when compared to the control group in the three areas assessed, with statistical difference (p <0.05). There was no statistical difference between the groups when evaluating the difference in BMD at the femoral neck and proximal femur in one year, the COPD group had a median of 0.003 g/cm2 (- 0.02 to 0.03) in the lumbar spine and -0.006 g/cm2 (-0.02 to 0.009) in the proximal femur, CG, respectively 0.011 g/cm2 (-0.01 to 0.04) and -0.006 g/cm2 (-0.02 to -0.007). As for bone loss at one year follow-up, there was no statistical difference between the groups, 16% in the COPD group and 20% in the control group, with p = 0.70. We also found no association between bone loss and factors associated with osteoporosis. Conclusion: Although patients with COPD have higher prevalence of osteoporosis than control subjects, and lower BMD values in all areas assessed, COPD and factors associated with the disease, they do not appear to influence the evolution of bone loss in one year.